Analysis of Nursing Documentation Implementation In Outpatient Room - Nurudin, Muhamad; Pohan, Vivi Yosafianti; Hartiti, Tri (South East Asia Nursing Research, 2020)
The quality of nursing care is a key element of service quality in hospitals. To realize good quality nursing service and quality in the Outpatient Institution, qualified human resources are also needed and good nursing management skills are needed from a manager or head of the service unit. For the implementation of nursing care documentation in outpatient installations to be carried out optimally, it is necessary to carry out management activities in the form of supervision by carrying out nursing support activities in stages. The purpose of this analysis is to determine the implementation of outpatient nursing medical record documentation. The use of action methods in this analysis aims to develop new skills or new approaches and be applied directly and reviewed the results. From the results of the assessment found several nursing management problems and the priority is the completeness of outpatient nursing medical record documentation which is still low. The action taken is by providing refresher activities or material refreshing on nursing documentation, initial assessment of outpatients, simulations of filling out initial outpatient assessment documentation, making and disseminating supervision forms and techniques for tiered supervision using the supervision form. The activity was attended by 23 participants consisting of the head of the room, the team leader and the nurse executing from the polyclinic or outpatient installation. Evaluation after carrying out activities on the completeness of outpatient nursing medical record documentation was 70%  (14 of 20 samples).